Patient-associated risk factors for severe anemia in patients with advanced ovarian or breast cancer receiving olaparib monotherapy: A multicenter retrospective study - Tashiro, Ryota; Kawazoe, Hitoshi; Mamishin, Kanako; Seto, Keisuke; Udagawa, Ryoko; Saito, Yoshimasa; Hashimoto, Hironobu; Shimoi, Tatsunori; Yonemori, Kan; Yonemura, Masahito; Terakado, Hiroyuki; Kawasaki, Toshikatsu; et al. (Frontiers in Oncology, 2022)
Background Olaparib-induced anemia is a frequently occurring complication in patients with advanced ovarian cancer, fallopian tube cancer, or primary peritoneal cancer and is associated with a marked deterioration in patients’ health-related quality of life. This study aimed to clarify patient-specific risk factors for severe anemia in patients with advanced ovarian or breast cancer receiving olaparib monotherapy in a real-world setting. Methods This multicenter, retrospective, observational study enrolled consecutively presenting patients with advanced ovarian or breast cancer who received olaparib monotherapy as maintenance or palliative treatment between April 2018 and December 2020 at three participating medical institutions in Japan. The primary endpoint was patient-associated risk factors underlying the onset of grade ≥3 anemia from olaparib treatment initiation to 90 days after treatment. Receiver operating characteristic curves were constructed and univariable and multivariable logistic regression analyses were performed to evaluate the association between patient-associated risk factors and grade ≥3 anemia. Results Of 113 patients evaluated in this study, 32.7% (n = 37) had grade ≥3 anemia. Multivariable logistic regression analysis revealed that low baseline red blood cell (RBC) count (<3.3 × 106 cells/μL), low baseline hematocrit level (<35%), low baseline hemoglobin level (<11.6 g/dL), and breast cancer susceptibility (BRCA1/2) mutation were significantly associated with the onset of grade ≥3 anemia (adjusted odds ratio [OR], 3.39; 95% confidence interval [CI], 1.28–9.62; P = 0.017, adjusted OR, 3.63; 95% CI, 1.28–11.64; P = 0.021, adjusted OR, 3.89; 95% CI, 1.39–12.21; P = 0.014, and adjusted OR, 4.09; 95% CI, 1.55–11.67; P = 0.006, respectively). Conclusions Our findings suggest that low baseline RBC count, low baseline hematocrit level, and low baseline hemoglobin level might be the patient-associated risk factors for severe anemia induced by olaparib monotherapy. Additionally, BRCA1/2 mutation was suggested to be a patient-related risk factor for anemia regardless of severity. Therefore, applying these patient-associated risk factors would help classify and screen patients at risk of severe anemia.